Edible Coating Chitosan as an Antimicrobial in the Thawing Process of Frozen Broiler Chicken Carcasses with Different Shelf Life - Tampubolon, Yusni Khairani; Nasution, Zakiyah -; Alawiyah, Erin - (Jurnal Ilmu Ternak Universitas Padjadjaran, 2023)
This study aims to determine the amount of chitosan edible coating concentration best used as antimicrobial during the thawing process of frozen broiler chicken carcass in different shelf lives. This study used a completely randomized factorial design (RALF) which consisted of two factors, namely factor 1: differences in shelf life (1, 2, and 3 months) and factor 2: concentration of chitosan edible coating (0.1 %, 1.5%) with 12 treatments and five replications. The total microbial count, pH, percentage of drip loss, and cooking losses of each sample were evaluated. The obtained data were analyzed using Two Way Analysis of Variance and further testing of the Duncan Multiple Range Test (DMRT). The results showed that frozen chicken carcasses using chitosan edible coating during thawing had a lower pH (P<0.05) than without chitosan. The use of 1.5% chitosan edible coating showed the best results (P<0.05) in inhibiting microbial growth, reducing drip loss and cooking shrinkage of frozen chicken carcass during storage of 1, 2 and 3 months. It was concluded that the use of chitosan edible coating was effective as an antimicrobial during thawing.